2015
DOI: 10.1016/j.matchemphys.2015.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the use of CaZrO3 as a facecoat material in the investment casting of TiAl alloys

Abstract: h i g h l i g h t sTo determine the interactions between CaZrO 3 filler and stucco materials during shell firing.To study the reaction between the CaZrO 3 facecoat and TiAl alloy during casting. The Al 2 O 3 stucco can react with CaZrO 3 filler to form (Zr, Ca)O 2 and CaAl x O y at 1650 C. O, Zr and Si ions from the ceramic moulds were observed to penetrate into the TiAl metal. The reaction products include (Ti, Zr) 5 (Al, Si) 3 and ZrAl 2 phase with high Ti ions solid solution. a b s t r a c tResearch was car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…Зокрема в [20] виявлено, що реакція форми на основі цирконату кальцію CaZrO 3 з титаном була дуже низькою. Дослідження [21] показали, що обсипка керамічних форм Al 2 O 3 реагувала з наповнювачем CaZrO 3 лицьового покриття, утворюючи (Zr, Ca)O 2 і CaAl x O y при температурі близько 1650 0 C. При використанні ZrO 2 в якості обсипки не спостерігалося взаємодії, за винятком деяких тріщин, що виникали в лицьовому покритті внаслідок зміни об'єму ZrO 2 під час його нагрівання. При дії титанового сплаву на лицьове покриття продукти взаємодії обсипки та наповнювача CaZrO 3 вступали в реакцію з титаном, внаслідок чого кисень проникав у сплав.…”
Section: проблеми технології формиunclassified
“…Зокрема в [20] виявлено, що реакція форми на основі цирконату кальцію CaZrO 3 з титаном була дуже низькою. Дослідження [21] показали, що обсипка керамічних форм Al 2 O 3 реагувала з наповнювачем CaZrO 3 лицьового покриття, утворюючи (Zr, Ca)O 2 і CaAl x O y при температурі близько 1650 0 C. При використанні ZrO 2 в якості обсипки не спостерігалося взаємодії, за винятком деяких тріщин, що виникали в лицьовому покритті внаслідок зміни об'єму ZrO 2 під час його нагрівання. При дії титанового сплаву на лицьове покриття продукти взаємодії обсипки та наповнювача CaZrO 3 вступали в реакцію з титаном, внаслідок чого кисень проникав у сплав.…”
Section: проблеми технології формиunclassified
“…4,5 However, the poor friction and wear behavior of TiAl alloy has been the obstacle for an increase in thrust load of TiAl alloy-made mechanical parts under some extreme conditions. 6,7 Friction reduction and wear resistance are two important parameters to analyze the tribological property of TiAl-based composites containing graphene, [8][9][10] silver, 11 and multiwalled carbon nanotubes (MWCNTs). 12,13 Many researchers such as Estrada-Ruiz et al 11 explored the friction and wear behavior of silver, and found that the lubrication property of silver was mainly determined by its shear strength and plastic deformation.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, for the purpose of further increasing service life of mechanical components in aerospace and aviation industries, the lubricating property of solid film has been received extensive concerns to realize the low friction and less wear of TiAl alloys (Yuan et al, 2015;Holmberg, 2009;Polcar et al, 2009;Kato et al, 2004;Beliardouha et al, 2015). Hence, it is important that the self-lubricating behavior and local failure of solid film is explored for further understanding the friction and wear property of TiAl alloys.…”
Section: Introductionmentioning
confidence: 99%